(untitled) (Cadernos de Sociomuseologia, 2015)
This article explores the process of patrimonialization and museification of the Hospital Colônia de Itapuã in the city of Viamão, Rio Grande do Sul, Brazil. This hospital, founded in 1940, was intended to treat patients suffering with hanseniasis (the term used in Brazil for leprosy). These patients, upon arrival to the institution, began to live within what was referred to as the “Colony”, a community formed within the hospital that contained dwellings, a school, religious temples, and small businesses. In the 1990’s the hospital gradually began to cease operating as an a place of isolation, however it maintained an area that was open to the residents and surrounding community. In order to celebrate the 60th anniversary of Itapuã, in the year 2000 a project was initiated to recuperate the memory of the old leper colony. This project culminated in the construction of a hospital memorial in 2014. Key-words: Museum. Cultural Heritage. Hospital Colônia Itapuã